UTILIZING A GENRE-BASED APPROACH TO IMPROVE EFL STUDENTS' READING COMPREHENSION AT A SECONDARY SCHOOL IN KARAWANG - Mila Fouri Aprilia, - (2023)
Reviewing PISA results, the reading ability of Indonesian students stands at a level where they can answer the simplest text comprehension questions. Still, they need help integrating and applying their ability to comprehend deeper texts or draw simple inferences. As a result, this study focuses on overcoming the problems by utilizing the genre-based approach to help EFL students improve their reading comprehension, especially at the literal, inferential, and evaluation levels. A qualitative approach with a classroom action research (CAR) design was conducted in two cycles. The research procedure includes planning, action, observation, and reflection. The participants in this study were six EFL students at a Junior High School in Karawang. The data was collected through students' reading tests, observation, and semi-structured interviews to answer the research question. The findings demonstrate that after GBA was implemented in the two cycles of action research, the student's perception of learning activities at the BKOF stage shows their interest in the topic discussed, which assists them in preparing for the context of the reading and creating a relationship between the reading and the reader's interest and background knowledge. Further, students can draw inferences and make arguments better through explanations and examples given at the deconstruction stage. Thus, the stages of deconstruction in GBA help students improve their reading comprehension, especially in literal, inferential, and evaluation understanding.